Pars pro toto. The literary Balkans in Europe: editor’s note (Colloquia Comparativa Litterarum, 2025)
This issue of the annual review Colloquia Comparativa Litterarum (the third since theinaugural one in 2015) has been composed in three parts:1. Pars pro toto. The Literary Balkans in Europe2. Miscellanea3. Book Reviews